Are intracranial pressure wave amplitudes measurable through lumbar puncture?. (11th July 2012) - Behrens, A.; Lenfeldt, N.; Qvarlander, S.; Koskinen, L.‐O.; Malm, J.; Eklund, A.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate whether pulsations measured in the brain correspond to those measured in lumbar space, and subsequently whether lumbar punctures could replace invasive recordings. Methods In ten patients with normal pressure hydrocephalus, simultaneous recordings of the intracranial pressure (ICP; intraparenchymal) and lumbar pressure (LP; cerebrospinal fluid pressure) were performed. During registration, pressure was altered between resting pressure and 45 mmHg using an infusion test. Data were analyzed regarding pulsations (i.e., amplitudes). Also, the pressure sensors were compared in a bench test. Results The correlation between intracranial and lumbar amplitudes was 0.98. At resting pressure, and moderately elevated ICP, intracranial pulse amplitudes exceeded that of lumbar space with about 0.9 mmHg. At the highest ICP, the difference changed to −0.2 mmHg. The bench test showed that the agreement of sensor readings was good at resting pressure, but reduced at higher amplitudes. Conclusions Compared to intracranial registrations, amplitudes measured through lumbar puncture were slightly attenuated. The bench test showed that differences were not attributable to dissimilarities of the sensor systems. A lumbar pressure amplitude measurement is an alternative to ICP recording, but the thresholds for what should be interpreted as elevated amplitudes need to be adjusted.